Düsseldorf. Metropolis on the Rhine. Urban development and city planning 2015 – 2020 – 2025. - Geisel, Thomas; Nellen, Dieter; Zuschke, Cornelia (Jovis, 2020)
Düsseldorf is growing and densifying, both economically and in terms of urban space. As in comparable European metropolises, this development drive harbors the opportunity to further distinguish architecture and city planning and to launch major projects—from the Blaugrüner Ring and the Kö-Bogen to the renaissance of the station district. The metropolis on the Rhine is not reinventing itself in the process but instead is gaining qualities: it is being oriented more strongly towards the river, and mixed residential and working quarters are being developed, as are concepts for contemporary mobility. This compact volume documents the current urban development strategies, formats, and projects for the decade 2015 to 2025 from the insider perspective of the municipal protagonists. In addition, architects, planners, and economists working in and for Düsseldorf, such as Ulrich Biedendorf, Christoph Ingenhoven, Andreas Kipar, Karl-Heinz Petzinka, and Christa Reicher, express their opinions on the current situation and the future of the city
Keywords: Stadtentwicklung; Städtebau; Projektübersicht; Neubau; Architektur; Stadtraum; Öffentlicher Raum